Rooting of olive minicuttings at different seasons grown in clonal minigarden - Casarin, Josiane Vergara; Ramm, Aline; Raasch, Carlos Gustavo; Timm, Cari Rejane Fiss; Schuch, Márcia Wulff (Comunicata Scientiae, 2018)
The objectives were: a) to evaluate the initial development of olive ministumps in semi-hydroponic and conventional systems; b) evaluate the productivity ministumps in successive collections and the rooting of minicuttings of olive tree collected at different times of the year clonal mini garden cultivated in semi-hydroponic and conventional systems. The cultivation systems used were the semi-hydroponics and conventional, to which was evaluated for 90 days of cultivation the initial growth of ministumps. After that began the collection of plant material in cropping systems. The variables analyzed were: the initial growth of ministumps, productivity, the percentage of survival and rooting, the number and length of roots and also found the survival of rooted minicuttings of cropping systems. The cultivation of olive ministumps in semi-hydroponic system is more efficient in minicuttings productivity than the conventional system. The minicuttings collected in separate semi-hydroponic system collecting time showed the best results for the variables analyzed in relation to the conventional system of cultivation.